Associação de fármacos e soro antiofídico no tratamento do envenenamento botrópico em coelhos - Warley Gomes dos Santos (2017)
Snakebite accidents are a public health problem in many tropical regions of the planet and may be fatal. In addition to attacking man, snake accidents also affect domestic animals. The research for therapeutic strategies and drugs that may contribute to the antagonization of the deleterious effects of snake venom on hemostatic and other organic systems are practically non-existent. Thus, the study of drugs adjuvants such as tranexamic acid and desmopressin are of great importance, since they have proven activity on the haemostatic system reducing hemorrhages of varied origins and being easily accessible. In this context, this study aims to evaluate if the use of these drugs promotes some benefit when used in cases of Bothrops alternatus snake envenomation in an experimental model of rabbit envenomation. Hematologic tests, haemostasis tests including the thrombin generation assays biochemical tests and histopathology of the skeletal striated muscles, lungs, liver, heart and kidneys were performed. For this, 36 rabbits, New Zealand, were distributed in different experimental groups, namely: G1- Group without induction of envenomation and treated with tranexamic acid; G2- Group without induction of envenomation and treated with desmopressin; G3- Group without induction of envenomation and treated with antibotropic serum; G4- Group B. alternatus without treatment; G5- Group B. alternatus treated with tranexamic acid; G6- Group B. alternatus treated with desmopressin; G7- Group B. alternatus treated with antibotropic serum; G8- Group B. alternatus treated with antibotropic serum + tranexamic acid; G9- Group B. alternatus treated with antibotropic serum + desmopressin. The experimental protocol consisted of the inoculation of the venom via the superficial intramuscular in the thigh of the animals and, therefore, each group received its respective treatment. The study shows that the venom of snake B. alternatus acts on hemostasis and coagulation promoting an imbalance, since the generation of thrombin was reduced in animals receiving venom. The drugs used did not improve the hemostasis and the animals treated with tranexamic acid or desmopressin presented thrombin generation also reduced and similar to the G4 group that received venom and was not treated. All animals in the study receiving venom presented haemorrhage at the venom inoculation site with inflammation and necrosis. It is inferred that the venom used in the study promoted cell death in the skeletal striated musculature by apoptosis being positive for caspase-3. In addition to local hemorrhage, several animals had pulmonary hemorrhage. Only the G4 group showed elevation of urea and creatinine levels, however, in the other groups no change was observed. Elevated glucose and triglyceride levels were also observed in certain groups, suggesting a metabolic imbalance. It is concluded that the drugs used in this study as coadjuvants in the treatment of snakebite accidents by Bothrops alternatus are not beneficial to the hemostatic system.